2012
DOI: 10.1136/annrheumdis-2012-201893
|View full text |Cite
|
Sign up to set email alerts
|

Timing the therapeutic window of opportunity in early rheumatoid arthritis: proposal for definitions of disease duration in clinical trials

Abstract: The effects of treatment in early rheumatoid arthritis (RA) and the consequences of delayed therapy represent important areas for research. The concept of a 'window of opportunity' is now well established and considerable attention has been paid to when it might close. However, in order to study how long the window of opportunity lasts, the timing of its opening must be precisely defined. An analysis of definitions of 'onset' in clinical studies reveals imprecision and heterogeneity, making accurate assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 35 publications
(28 reference statements)
0
39
0
Order By: Relevance
“…Symptom onset in EAC and ESPOIR was delineated identically and defined as the first musculoskeletal symptom (either being pain or swelling) relevant to the current presentation 13. The symptom duration was defined as the duration between this patient reported symptom onset and inclusion and was determined by subtraction of dates, expressed in weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Symptom onset in EAC and ESPOIR was delineated identically and defined as the first musculoskeletal symptom (either being pain or swelling) relevant to the current presentation 13. The symptom duration was defined as the duration between this patient reported symptom onset and inclusion and was determined by subtraction of dates, expressed in weeks.…”
Section: Methodsmentioning
confidence: 99%
“…8,9,[22][23][24] It has been shown that the earlier patients with RA are treated the more effective is the treatment. 25,26 Thus there is an urgent need for a very early diagnosis of RA in order to enable earlier treatment and to reduce or even to stop the progress of the disease. Furthermore, an early diagnosis can prevent joint damage, thereby lowering the additional therapeutic and disability costs which arise from reduced work capacity of the patients: nearly 30% of patients give up work within 1 year as a result of their condition and almost 60% within 6 years of diagnosis.…”
mentioning
confidence: 99%
“…Current recommendations for patients with poor prognostic factors suggest treatment with MTX for 3 to 6 months before considering the addition of biologic DMARD therapy 12 , but some rheumatologists continue MTX for longer periods before considering the addition of biologic therapy 13,14 . For patients early in the course of disease (< 3 years' duration), there may be a window of opportunity (estimated to be at least 6 months) during which the timely addition of anti-TNF therapy to MTX-inadequate responders can result in optimal therapeutic responses 15 . However, a 2-year delay appears to exceed this window, resulting in an inability to improve outcomes 16 .…”
mentioning
confidence: 99%